Histological, physiological and transcriptomic analysis in hepatopancreas of Procambarus clarkii under heat stress - Yongfeng Zou; Panhui Cao; Zhiming Bao; Yu Xu; Zhiqiang Xu; Hui Guo (Ecotoxicology and Environmental Safety)
In the context of global warming, heat stress poses a threat to aquatic organisms. In the present study, a comprehensive analysis in hepatopancreas from Procambarus clarkii was conducted to examine the histology, physiological changes, and transcriptome alterations after exposed at 32 and 37 ℃ for 24 and 72 h, respectively, with 26 ℃ as the control group. The results demonstrated that the survival rate of P. clarkii decreased significantly with the stress time and the temperature increased, with a corresponding damage to its hepatopancreas. Significant fluctuations were observed in the malondialdehyde (MDA) content, reactive oxygen species (ROS) production, total antioxidant capacity (T-AOC), and activities of pyruvate kinase (PK), hexokinase (HK), alkaline phosphatase (ALP), lysozyme (LYS), acid phosphatase (ACP), fatty acid synthase (FAS), as well as lipoprotein lipase (LPL) in response to different stress conditions (P < 0.05). Heat stress notably altered the expression of genes related to glucose, lipid, and protein metabolism, as well as oxidative phosphorylation pathways. The expression of genes related to protein processing and degradation pathways in the endoplasmic reticulum was up-regulation. On the contrary, the expression of genes related to ER autophagy was suppressed. Simultaneously, the differentially expressed genes (DEGs) were significantly enriched in lysosomal and phagosomal pathways. In summary, heat stress induced oxidative damage, disrupted metabolic pathways, impacted protein processing, and compromised immune defense mechanisms, ultimately resulting in decreased survival rates of P. clarkii. These findings contribute to a deeper understanding of aquatic organisms respond to heat stress.